FUMARATE REDUCTASE INHIBITORY POTENTIAL OF PHYTOSTILBENES, RESVERATROL AND ΑLFA-VINIFERIN - BISHNUPADA ROY; BIKASH RANJAN GIRI (International Journal of Pharma and Bio Sciences, 2016)
Parasitic helminthes have several unique enzymes associated with energy transducing pathways, which can act as a selective target for chemotherapeutic agents. Resveratrol and its trimer α-viniferin are two phytostilbenes, known to alter ultrastructure and activities of tegumental enzymes in helminth parasites. The present study was carried out to see the effects of these phytostilbenes on the activity of fumarate reductase, an enzyme of anaerobic electron transport system in helminth mitochondria. Exposure of R. echinobothrida to resveratrol (0.136 mg/ml) and α-viniferin (0.135mg/ml) causes a reduction in the activity of fumarate reductase to an extent of 51.77 and 68.501% in the exposed parasites as compared to the controls, respectively. Praziquantel (0.135 mg/ml), the reference anthelmintic drug, also reduce the activity by 24.157%. The present study indicates that resveratrol and α-viniferin are potential anthelmintics, which target mitochondrial complex II enzyme leading to energy deficiency and paralysis of the parasites.